Effect of Cooperative Learning Supported by Reflective Thinking Activities on Students' Critical Thinking Skills - Erdogan, Fatma (Ani Yayincilik, 2019)
Purpose: It is assumed that cooperative work and critical thinking skills will come into prominence in 2020. In this context, the aim of this study is to examine the effect of cooperative learning supported by reflective thinking activities on seventh grade students' critical thinking skills during mathematics course. Method: In this study, a quasi-experimental model with pretest-posttest control group was applied. In the experimental group, cooperative learning method supported by reflective thinking activities was applied. In the control group, mathematics teaching was carried out in accordance with the curriculum of the mathematics course. The study group was composed of 70 seventh grade students. Cornell Critical Thinking Test, Level X was used as the data collection tool. Dependent and independent samples t-tests were used in data analysis, and ANCOVA was applied to determine the difference between the post-tests scores of the groups. Findings: In the study, when the pre-test scores of the experimental and control groups were checked, a significant difference was found between the corrected CCT-X post-test mean scores. This difference was found to be in favor of the experimental group. Based on this finding, cooperative learning supported by reflective thinking activities can be said to have a positive effect on students' critical thinking skills. Implications for Research and Practice: In future research, the effects of different reflective thinking strategies on critical thinking skills can be examined in cooperative learning environment, and their advantages and disadvantages can be discussed. Student's critical thinking skills can be analyzed by qualitative methods. (C) 2019 Ani Publishing Ltd. All rights reserved
Yansıtıcı Düşünme Etkinlikleriyle Desteklenen İşbirlikli Öğrenmenin Öğrencilerin Eleştirel Düşünme Becerileri Üzerine Etkisi
Keywords: Mathematics education; higher order thinking skills; jigsaw technic; middle school